Commitment and Goals - Peacock, Mark; Justus Liebig University Giessen (My University, 2013)
In this Comment, I examine Christoph Hanisch's recent contribution to this journal. In commenting on Hanisch's essay, I offer an interpretation of Amartya Sen's notion of `commitment' which makes committed choices both uncontroversial and quotidian. This interpretation contrasts with those which see some of Sen's pronouncements on commitment to be obviously false, counterintuitive or psychologically impossible.
Keywords: Commitment; self-goal choice; Amartya Sen; rational choice; ddc:100; ddc:330